Functional Studies of Novel FOXL2 Variants in Chinese Families With Blepharophimosis–Ptosis–Epicanthus Inversus Syndrome - Li, Fang; Chen, Huifang; Wang, Yefei; Yang, Jie; Zhou, Yixiong; Song, Xin; Fan, Jiayan (Frontiers in Genetics, 2021)
The blepharophimosis–ptosis–epicanthus inversus syndrome (BPES) is a rare autosomal dominant disease mainly caused by FOXL2 variants. This genetic disorder is usually characterized by eyelid malformation and ovarian dysfunction. However, no reliable genotype/phenotype correlations have been established considering the ovarian phenotype. Here, we detected 15 FOXL2 variants including nine novel ones from 7 families and 8 sporadic cases, which expanded the spectrum of FOXL2 variants and identified a potential clinical cause. Functional studies, with respect to the effect of FOXL2 on the StAR promoter, showed that non-sense variants that lead to protein truncation before the polyalanine tract and missense variants [c.307C > T; p.(Arg103Cys), c.311A > C; p.(His104Pro), c.320G > A; p.(Ser107Asn), and c.335T > A; p.(Phe112Tyr)] within the central portion of the FOXL2 forkhead domain significantly affect its suppressor activity. Such changes may explain the mechanism underlying a more severe phenotype, more likely to result in BPES type I. Furthermore, the missenses variants c.307C > T; p.(Arg103Cys), c.311A > C; p.(His104Pro), and c.320G > A; p.(Ser107Asn) were not able to transactivate OSR2, which is consistent with the eyelid malformation in these patients. The results from our cohort have expanded the spectrum of FOXL2 variants and have provided insights into genotype/phenotype correlations.